Faktor-Faktor yang Mempengaruhi Prestasi Akademik Mahasiswa Diploma Keperawatan - Astuti, Ayu Prameswari Kusuma; Aisyah, Iis (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Achievement can be a gateway to achieving higher education, a career, or job opportunities. Students’ exam scores that do not meet the university's minimum limit affect academic achievement results. This study aimed to identify which factors most significantly influence nursing students’ academic achievement. This study used a cross-sectional design, with 158 samples selected from second- and third-year diploma nursing students. A modified survey questionnaire was distributed online to collect data. Data analysis was performed using descriptive statistics and simple and multiple linear regressions. The results showed that teacher factors were the most influential on academic achievement compared to 3 other factors such as student-related factors, home-related factors, and school-related factors, with a t-value of 3.274 (β = 0.301, p = 0.001, R² = 0.27). This study concludes that teacher factors have the greatest influence on learning achievement. Suggestions for students are to be proactive, build independent learning strategies, and optimally utilize campus facilities.